Data center watchdog - Marambire, Nyasha (Midlands State University, 2019)
The past decade has been characterised by many firms migrating to clouding services which are powered by data centers. This led to a vast growth rate in the number of data centers in the world and as a result data centers became the most energy consuming facilities. Researches conducted by different scholars reflected that these energy consumptions can be reduced by using free cooling in data centers and raising the data center operating temperatures but however both methods result in an increased rate or probability of occurrence of hotspots. It therefore follows that a mechanism to quickly detect hotspots and reduce their impact was required to be put in place and this research focused on development of an Arduino based data center watchdog system written in C and C++ that could continuously monitor the rack inlet temperature and humidity levels as well as protect the equipment in the affected racks. The watchdog was successfully developed and it was recommended that before deploying it the technicians should first do CFD calculations in order to account for temperature variations as well as installing DHT22 in every rack in order for all rack temperature and relative humidity values to be accounted for. In the future it is recommended that the system be interlinked with cooling system in order to allow it to automatically calibrate the cooling system variables.